Development and performance of graphene oxide (GO)/hexagonal molybdenum trioxide (h-MoO3)/silicon dioxide (SiO2)/magnetite (Fe3O4) magnetic composite photocatalyst in degradation of methylene blue and phenol under visible light - Antonio, Rheamay V.
Photocatalysis is a well-known approach for the degradation of pollutants where light energy is utilized to excite the semiconductor to produce electron/hole pair. Existing well-known photocatalyst is characterized by wide band gap, which restricts the solar light utilization. In this study, a magnetic nanocomposite material using magnetite (Fe3O4) as core, with an interlayer of silicon dioxide (SiO2) and hexagonal molybdenum trioxide (h-MoO3) nanoshell dispersed with functionalized graphene oxide (GO), (FSM-GO) was synthesized. Response surface methodology (RSM) was used to optimize FSM-GO synthesis. The ability of the optimized FSM-GO photocatalyst to degrade methylene blue (MB)and phenol were also studied. Batch experiments were performed to obtain responses in terms of percent removal for both adsorption and photocatalysis. The photocatalysis was conducted under visible light irradiation. A second order polynomial equation was used to model the relationship between the synthesis conditions and the responses. High coefficient of determination (R²) values of 0.84 and 0.94 were obtained for adsorption and photocatalysis, respectively. The result FSM-GO synthetic products were characterized by FT-IR spectroscopy, SEM, and band gap estimation, evidencing the successful synthesis of a photocatalytic nanocomposite. The effects of photocatalyst dosage, initial MB concentration, and pH were investigated, and 99.22% MB removal was obtained. Results showed that experimental data followed a pseudo-first order kinetic model. FSM-GO demonstrated 30% microbial inactivation against E. coli. It was established that the antimicrobial property of these nanocomposites is due to the production of reactive oxygen species.